Networked Learning for Post-Graduate Supervisors - Kandlbinder, Peter (Proceedings of the International Conference on Networked Learning, 2000)
The Postgraduate Supervisors Development Program has been delivered on-line since 1998. The success of this program in demonstrating the potential for on-line academic staff developme11t has led the Institute for Teaching and Learning to undertake further on-line initiatives targeting, in the first instance, flexible learning and assessment. This paper discusses the development of this networked learning program in which academic staff are free to arrange their own progression and retrieve resources at any time that suits them and their supervisory responsibilities. It highlights the program’s participatory modes of learning that creates an environment in which supervisors can reflect on their own supervision as a basis for understanding their supervisory practice.